Odpowiedzi

Najlepsza Odpowiedź!
2009-12-10T17:36:45+01:00
{2x+y=9 |*4
{5x-4y=3

8x + 4y = 36
5x - 4y = 3
13x = 39 |:13
x = 3

2x +y = 9
2*3 + y = 9
y = 9-6
y = 3

________ C
{x-2y=3|*2
{-2x+y=0

2x - 4y = 6
-2x + y = 0
-3y = 6 |:(-3)
y = -2

_______ B
{x+4y=-2 |*2
{3x-8y=10

2x + 8y = -4
3x - 8y = 10

5x = 6|:5
x = 1,2

x + 4y = -2
1,2 + 4y = -2
4y = -2 - 1,2
4y = -3,2 |:4
y = -0,8
2009-12-10T17:41:10+01:00
2x+y=9 /*4
5x-4y=3

8x+4y=36
5x-4y=3
------------dodajemy
13x=39
x=3

2x+y=9
y=9-2x
y=9-6
y=3
------------

{x-2y=3 /*2
{-2x+y=0

2x-4y=6
-2x+y=0
-------------- dodajemy
-3y=6
y=-2

x-2y=3
x=3+2y
x=3-4
x=-1


---------------


{x+4y=-2 /*2
{3x-8y=10

2x+8y=-4
3x-8y=10
-----------dodajemy
x=6

x+4y=-2
4y=-2-x
y=-1/2-1/4x
y=-1/2-1/4*6
y=-2